The Game-Changing Effect of Mobile Money on Shaping Financial Knowledge And Financial Skills - Alatas, Rahman; Valentino, Valentino; Elliyana, Ela; Maricar, Rezvanny (IJHCM (International Journal of Human Capital Management), 2023)
The purpose of this study was to determine the effect of mobile money on financial knowledge and financial skills.The approach used in this research is a quantitative approach. The method used is a survey by distributing questionnaires to 100 respondents who are active mobile money users in Indonesia. The research instrument used was a questionnaire using a five-level Likert scale. In this study, researchers took a random sampling technique, namely random sampling so that it was not limited but could represent the entire population, workers, housewives active students. Data analysis and hypothesis testing were carried out using multiple linear regression analysis techniques, partial tests and simultaneous tests using the SEM PLS 4 application. The results showed that mobile money has an effect on financial knowledge and financial skills in active smarthpone users who are used for money transfer transactions, purchases in e-commerce, bill payments. The convenience of mobile money services, such as quick and easy transactions and bill payments.